Supporting self-management of low back pain with an internet intervention in primary care: a protocol for a randomised controlled trial of clinical and cost-effectiveness (SupportBack 2). Issue 8 (20th August 2020) - Geraghty, Adam W A; Roberts, Lisa; Hill, Jonathan; Foster, Nadine E; Yardley, Lucy; Hay, Elaine; Stuart, Beth; Turner, David; Griffiths, Gareth; Webley, Frances; Durcan, Lorraine; Morgan, Alannah; et al.
Abstract : Introduction: Self-management and remaining physically active are first-line recommendations for the care of patients with low back pain (LBP). With a lifetime prevalence of up to 85%, novel approaches to support behavioural self-management are needed. Internet interventions may provide accessible support for self-management of LBP in primary care. The aim of this randomised controlled trial is to determine the clinical and cost-effectiveness of the 'SupportBack' internet intervention, with or without physiotherapist telephone support in reducing LBP-related disability in primary care patients. Methods and analysis: A three-parallel arm, multicentre randomised controlled trial will compare three arms: (1) usual primary care for LBP; (2) usual primary care for LBP and an internet intervention; (3) usual primary care for LBP and an internet intervention with additional physiotherapist telephone support. Patients with current LBP and no indicators of serious spinal pathology are identified and invited via general practice list searches and mailouts or opportunistic recruitment following LBP consultations. Participants undergo a secondary screen for possible serious spinal pathology and are then asked to complete baseline measures online after which they are randomised to an intervention arm. Follow-ups occur at 6 weeks, 3, 6 and 12 months. The primary outcome is physical function (using the Roland and Morris Disability Questionnaire) over 12 months (repeated measures design). Secondary outcomes include pain intensity, troublesome days in pain over the last month, pain self-efficacy, catastrophising, kinesophobia, health-related quality of life and cost-related measures for a full health economic analysis. A full mixed-methods process evaluation will be conducted. Ethics and dissemination: This trial has been approved by a National Health Service Research Ethics Committee (REC Ref: 18/SC/0388). Results will be disseminated through peer-reviewed journals, conferences, communication with practices and patient groups. Patient representatives will support the implementation of our full dissemination strategy. Trial registration number: ISRCTN14736486 .